Purchase Decision dan Repurchase Intention: Analisis Bibliometrik Faktor Digital Marketing - Nia Valentina; Lissa Rosdiana Noer (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
The advancement of digital technology has driven a major transformation in marketing strategies, positioning digital marketing as a primary approach in shaping consumer purchase decisions and repurchase intentions. Although numerous studies have explored the influence of digital marketing on purchase intention, systematic research that connects digital marketing with repurchase intention through bibliometric analysis remains limited. This study aims to analyze trends, dominant themes, and scientific contributions in the literature related to purchase decision and repurchase intention within the context of digital marketing. The method used is bibliometric analysis with a descriptive quantitative approach, utilizing data from Scopus. The findings reveal a significant increase in publications since 2018, peaking in 2025. Key themes identified include customer satisfaction, service quality, perceived value, and decision making, all closely linked to repurchase intention. China and Indonesia are noted as the top contributing countries, while authors such as HAN H. and LEE J. demonstrate consistent productivity. Keyword network visualization and thematic analysis show that repurchase intention is a central focus in the literature, supported by various consumer behavior variables. The study concludes that digital marketing plays a crucial role in fostering consumer loyalty, and bibliometric analysis provides a comprehensive overview of the direction and development of research in this field.